Konteks Teguran Allah terhadap Nabi Muhammad dalam Al-Qur’an - Rima Annisa; Zulihafnani Zulihafnani (TAFSE: Journal of Qur'anic Studies, 2020)
Prophet Muhammad is a messenger of God who carries the trust to deliver the message and be an example for all mankind. On the other hand, in certain contexts the Prophet Muhammad also received a rebuke from Allah for the mistake of his attitude. This paper aims to explain the opinion of the commentator on the rebuke and in what context the Prophet Muhammad received a rebuke from God. This research is qualitative by examining various sources of tafsir books. The results of this study show that God's rebuke to the Prophet is intended as a teaching and refinement of the Prophet's personality. The author finds several contexts about Allah's rebuke to the Prophet Muhammad in the Qur'an, namely about the Prophet's sour-faced attitude towards Ummi Maktum, giving permission to the hypocrites not to take part in the war, performing pray for the hypocrites who died in disbelief, asking for forgiveness for the polytheists, moving the tongue during the revelation of verses, cursing the polytheists, desiring the spoils of war, making treaties with the polytheists of Mecca without accompanying them with the word ‘Insyā Allāh’ and forbidding things that are lawful by Allah. The various rebukes are recorded in the Qur'an in various contexts, and this proves that the Qur'an is not the work of the Prophet, but he is the recipient of revelation from God and shows that the Prophet Muhammad was a weak creature before God. Nabi Muhammad merupakan salah seorang utusan Allah yang mengemban amanah untuk menyampaikan risalah serta menjadi contoh teladan bagi seluruh umat manusia. Di sisi lain, pada konteks tertentu Nabi Muhammad juga mendapat teguran dari Allah atas kekeliruan sikap yang dilakukan. Tulisan ini bertujuan untuk menjelaskan pendapat mufasir terhadap teguran tersebut dan dalam konteks apa saja Nabi Muhammad mendapat teguran dari Allah. Penelitian ini bersifat kualitatif dengan mengkaji berbagai sumber dari kitab tafsir. Hasil penelitian menunjukkan bahwa teguran Allah terhadap Nabi dimaksudkan sebagai pengajaran dan penyempurnaan kepribadiannya. Beberapa konteks teguran Allah terhadap Nabi Muhammad dalam al-Qur’an adalah sikap Nabi yang bermuka masam terhadap Ummi Maktum, memberi izin kepada orang-orang munafik untuk tidak ikut berperang, melakukan salat terhadap munafik yang mati dalam keadaan kafir, meminta ampunan bagi orang-orang musyrik, menggerakkan lisan ketika turun wahyu, melaknat orang-orang musyrik, menghendaki harta rampasan perang, membuat perjanjian dengan orang-orang musyrik Mekah tanpa mengiringi dengan kata ‘Insyā Allāh’ dan mengharamkan hal yang dihalalkan oleh Allah. Berbagai teguran tersebut terekam dalam al-Qur’an dalam berbagai konteks, dan ini membuktikan bahwa al-Qur’an bukanlah hasil karya Nabi Saw., tetapi ia adalah penerima wahyu dari Allah serta menunjukkan bahwa Nabi Muhammad merupakan makhluk yang lemah di hadapan Tuhan-Nya.